Crown square microstrip fractal antenna / Amira Putri Mohammad - Mohammad, Amira Putri (1996)
This paper presents the design of a crown square fractal antenna (CSFA) for wireless applications. This CSFA was fabricated on FR4 substrate with dielectric constant of Zjc = 4.7 and thickness, h = 1.6 mm. All the design and simulation was carried out by using a commercial electromagnetic simulator, CST Microwave Studio. Measurements of the parameter of this antenna was carried out by using Vector Network Analyzer (VNA). It was observed that, both the measured and simulated values of the parameters of the antenna were close each other and compact size antenna was realized.